Anaerobic biodegradation of decabromodiphenyl ether (BDE-209)-contaminated sediment by organic compost. (September 2016) - Chang, Yi-Tang; Lo, Tsui; Chou, Hsi-Ling; Laio, Yi-Fen; Lin, Cheng-Chun; Chen, Houng-Toung
Abstract: Polybrominated diphenyl ethers (PBDEs), commonly used as a flame retardants for industrial and commercial products, have a strong tendency to accumulate in the interface of water/soil/sediments and are difficult to biodegrade. An effective biological treatment for PBDE removal is needed. In this study, we investigated the use of 3 organic compost materials (BM-2, BM-6, and BP-2) to remove 20 mg kg −1 decabromodiphenyl ether (BDE-209) from contaminated sediment in anaerobic microcosms for 120 days and detected the bacterial community in samples. Organic substance of compost had sorption and biodegradation ability. BM-6 showed the highest sorption of BDE-209, at 38.95%, and BM-3 the highest biological activity, at 34.90%. Methylophilus spp., Pseudomonas spp., Clostridium spp., and Dehalococcoides sp. were identified in anaerobic microcosms with PBDE biodegradation. The pathway of anaerobic DBDE biodegradation from higher to lower brominated PBDE was identified by the appearance of PBDE biometabolites and functional genes related to reductive debromination. We have identified an effective approach for bioremediating PBDE-contaminated sediment by using organic compost; this approach is highly recommended for practical engineering for off-site remediation. Highlights: This is the first study of BDE-209 biodegradation by organic composts. Debromination pathway for anaerobic BDE-209 biodegradation was identified. Dominant bacteria responsible for anaerobic BDE-209 biodegradation are detailed. Practical off-site bioremediation of BDE-209-contamination can be developed.